Breaking Up - Cooke, Stuart (University at Albany, 2022)
Research Background: 'Breaking Up' was composed during the onset of the COVID-19 pandemic in Italy. Via a variety of methods such as collage, fragment and memoir, the piece explores the relationship between the end of empire, late capitalism, climate collapse and anxiety disorder(s). The form was inspired in part by writers like David Shields and Sven Linqvist, but unlike Shields and Linqvist, perhaps, I am more invested in the weight of the first-person, and in how this weight can lead to a kind of lyric force, or prose poetry. Research Question: ‘Breaking Up’ grapples with how the lyric ‘I’ might expand (or be ruptured) to gesture towards a public 'we' and then, should that be possible, how such publics might be imagined in the face of rapidly accelerating rates of ecological decay. Formally, this problem is reflected in the piece’s unsettled relation with linearity, fragment and quotation. Thus, experience is articulated as series of inter-linked scenes and interludes rather than via linear narration, and it is as broken up across past and present temporalities as it is across various regions of the globe. Consequently, the piece is both a diary of an unfolding crisis and an echo of much deeper and more pervasive tendencies of Western capitalism. Research Significance: ‘Breaking Up’ links a variety of anthropogenic phenomena including the breaking up of Antarctic ice sheets, the ruins of Ancient Rome, and the fragmentation of social space and individual wellbeing, which accelerated under the first COVID lockdowns. It also proposes provocative reinterpretations of subjectivity, which might be necessary to avoid further crises. ‘Breaking Up’ was published in Barzakh, a leading international literary journal of experimental writing. Based at SUNY Albany, USA, Barzakh is a multi-genre journal with an internationalist stance. They publish “work that transcends genre,” with a focus “on innovative and experimental poetry and prose as well as socially engaged art.” No Full Text